2020
DOI: 10.1002/ecy.2956
|View full text |Cite
|
Sign up to set email alerts
|

Rare microbial taxa emerge when communities collide: freshwater and marine microbiome responses to experimental mixing

Abstract: Whole microbial communities regularly merge with one another, often in tandem with their environments, in a process called community coalescence. Such events impose substantial changes: abiotic perturbation from environmental blending and biotic perturbation of community merging. We used an aquatic mixing experiment to unravel the effects of these perturbations on the whole microbiome response and on the success of individual taxa when distinct freshwater and marine communities coalesce. We found that an equal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 58 publications
11
51
0
Order By: Relevance
“…In our study we tried to mimic natural dispersal events of bacterial communities which are often complex and involve mixing or coalescence of entire communities (Rillig et al, 2015; Rocca et al, 2020). This study provides experimental evidence that temperature‐dependency of invasion (immigration) success can occur in complex pelagic bacterial communities wherein different bacterial groups are involved in different ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study we tried to mimic natural dispersal events of bacterial communities which are often complex and involve mixing or coalescence of entire communities (Rillig et al, 2015; Rocca et al, 2020). This study provides experimental evidence that temperature‐dependency of invasion (immigration) success can occur in complex pelagic bacterial communities wherein different bacterial groups are involved in different ways.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter case, dispersal initiates species sorting processes even at very low rates of dispersal (Declerck et al, 2013), which eventually selects species that are better adapted to the given environment. All these processes can play an important role whenever mixing of communities (known as “community coalescence”) occurs (Rocca et al, 2020). Such community interchange events vary in the extent to which the environments of the coalescing communities are involved in the exchange, the mixing ratio of the communities, as well as temporal aspects of the event, which then all influence the resulting species establishments, exchanges and extinctions (Rillig et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of rare taxa seems to be a shared coalescence outcome between different ecosystems, i.e. for the mixing of freshwater and marine microbiome (29), the unequal mixing of two soils with different physicochemical and microbial compositions (69) or the mixing of soils for the outcome of rhizobial communities on rooibos nodules (70). Rare taxa becoming dominant can provide essential or new functions in nutrient cycling or plant growth, which replace or compensate for the function deficiency of abundant species (71).…”
Section: Discussionmentioning
confidence: 99%
“…The encounter between two microbial communities and how they then evolve together has been called community coalescence (2729). The outcomes of community coalescence can vary in a continuum between two categories from symmetric to asymmetric outcomes (30).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a growing body of research has emphasized the ecological importance of rare taxa (Lynch and Neufeld, 2015;Jousset et al, 2017), and distinct succession patterns and functional characteristics were found in abundant and rare taxa (Jia et al, 2018;Jiao and Lu, 2020b;Rocca et al, 2020). The abundant taxa are usually perceived as the most active category in biogeochemical cycles, especially carbohydrate metabolism, and take up the coring niche (Jiao et al, 2017;Kurm et al, 2019;Liang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%